DEVELOPMENT OF CANVA-BASED NEWS TEXT MODULE FOR CLASS VIII SMP STUDENTS - Nisrina Ida Alifah; Fathiathy Murtadho; Reni Oktaviani; Reni Nur Eriyani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This study is to perceive the development of the news text e-module Canva-Based in class VIII SMP. This research uses Research and Development method based on the ADDIE model developed by Branch. The analysis stage, a curriculum used, learning materials, and news texts. The design stage contained a framework and display of developed learning materials and news text using a scientific approach, including four language skills based on Canva. It has fundamental competencies, introduction, the structure of news text, grammar in news text, steps to make a news text into a news text, Evaluation, and Reference. The implementation stage requires validation by media and material experts before a test on teachers and students. The testing phase on Four Indonesian language teachers at SMPN 131 Jakarta and SMPN 175 Jakarta gave a response that can be used and great. Students at SMPN 131 Jakarta got a positive response with an average of 96.1% of 35 students. for SMPN 175 Jakarta obtained an average of 97% of 35 students. The results of the average assessment of students from SMPN 131 Jakarta and SMPN 175 Jakarta get a percentage score of 96%.